Learning factors influencing second language proficiency: a cross-cultural comparative study of English and Chinese L2 learners - Xuancheng Wu; Xin Wen; Juan Lu; Weizhi Liu (BMC Psychology)
Abstract Background Globalization has spurred a rise in second language (L2) learners, necessitating deeper understanding of psychological and cognitive factors shaping their learning processes. While prior research focuses predominantly on English second language (ESL) learners, studies involving learners of other languages remain scarce. This study bridges this gap by examining learning motivation, strategies, and styles across ESL learners and Chinese second language (CSL) learners. Methods We surveyed 312 learners, using the Strategy Inventory for Language Learning (SILL) and the Perceptual Learning Style Preference Questionnaire (PLSPQ), College English Test (CET) and the Hanyu Shuiping Kaoshi (HSK) to assess variables. Data were analyzed using SPSS for correlation and regression. Results Divergent patterns emerged between groups. For ESL learners, learning motivation directly shaped strategy use, which in turn were positively correlated with learning proficiency, with visual learning styles further enhancing the degree of proficiency. Conversely, CSL learners exhibited no significant motivation-strategy link, and learning strategies negatively predicted proficiency. However, group-based learning styles positively influenced CSL proficiency. Conclusions These results highlight that the impact of learning factors on proficiency varies across different L2 learners. Proficiency levels influence the choice of learning strategies and preferences. Consequently, teaching strategies should be dynamically adjusted to align with learners’ cultural backgrounds, proficiency levels, and individual learning factors, which can enhance the effectiveness of second language education and better support diverse learner needs. This study emphasizes the need for adaptive educational practices and further research. Keywords: Second language learning; Learning motivation; Learning strategy; Learning style; Learning proficiency.